Does the Cambridge Automated Neuropsychological Test Battery (CANTAB) Distinguish Between Cognitive Domains in Healthy Older Adults?. (April 2016) - Lenehan, Megan E.; Summers, Mathew J.; Saunders, Nichole L.; Summers, Jeffery J.; Vickers, James C.
The Cambridge Neuropsychological Test Automated Battery (CANTAB) is a semiautomated computer interface for assessing cognitive function. We examined whether CANTAB tests measured specific cognitive functions, using established neuropsychological tests as a reference point. A sample of 500 healthy older ( M = 60.28 years, SD = 6.75) participants in the Tasmanian Healthy Brain Project completed battery of CANTAB subtests and standard paper-based neuropsychological tests. Confirmatory factor analysis identified four factors: processing speed, verbal ability, episodic memory, and working memory. However, CANTAB tests did not consistently load onto the cognitive domain factors derived from traditional measures of the same function. These results indicate that five of the six CANTAB subtests examined did not load onto single cognitive functions. These CANTAB tests may lack the sensitivity to measure discrete cognitive functions in healthy populations or may measure other cognitive domains not included in the traditional neuropsychological battery.